Transforming Islamic Religious Education Through ChatGPT: Responding to Digital Learning Emergencies and Pedagogical Challenges in Indonesian Junior High Schools - Zainal Arifin; Akhmad Iqbal; Asmad Hanisy (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
This study explores the implementation of ChatGPT in Islamic Religious Education (IRE) learning at SMP Darussalam Kalibaru in response to digital learning emergencies and pedagogical challenges in Indonesian junior high schools. The research aims to analyze how artificial intelligence, particularly ChatGPT, is integrated into teaching practices, as well as its benefits, challenges, and educational implications. A qualitative case study approach was employed involving Islamic Religious Education teachers and students as key informants. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that ChatGPT is widely utilized by teachers in preparing lesson plans, instructional materials, and assessment instruments, thereby increasing efficiency and productivity in teaching activities. Students also use ChatGPT as a learning support tool to understand Islamic Religious Education materials more easily and independently. However, the study also identifies challenges such as students’ overreliance on AI-generated responses and the potential reduction of critical thinking skills. Despite these concerns, ChatGPT is generally perceived as a beneficial educational innovation when used under proper teacher guidance. The study concludes that ChatGPT serves as an effective supplementary tool in Islamic Religious Education, supporting the transformation of traditional pedagogy into a more interactive and technology-enhanced learning environment. Nevertheless, its implementation requires careful supervision to ensure ethical and responsible use. This research contributes to the growing discourse on artificial intelligence in education, particularly within religious education contexts, and highlights the importance of balancing technological innovation with pedagogical and moral values.